Reflecting on Partnerships of Sustainability Learning: Enacting a Lewin–Deleuze–Guattari Rhizome - Tillmanns, Tanja; Salomão Filho, Alfredo (Sustainability, 2020)
This paper works towards the enactment of a Lewin–Deleuze–Guattari rhizome. We assemble Deleuze and Guattari’s principles of the rhizome, Lewin’s idea of re-education, and reflections on the performance of one of the authors in the lecture hall, bringing into being what could be a rhizomatic partnership approach to sustainability learning in a higher education setting. The reflections are based on experiences delivering a sustainability module within a business education context, mainly for international students in Germany. The purpose of this paper is to illuminate possibilities of student–teacher partnership assemblages, aiming to motivate sustainability change agency on “people-yet-to-come”: those who are open to enacting difference, or multifaceted, heterogeneous, and often partial transformations addressing the current plethora of contemporary crises.<br
Keywords: rhizome; transformation; sustainability education; teacher–student partnership; change agency